ARABIC DISCOURSE MARKERS IN AL-JAZEERA.NET NEWS ARTICLE - Khairudin, Nuradlina Binti; Noor, Maizura Mohd; Abd Rahman, Ghazali Yusri (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2020)
This study investigates discourse markers (DMs) development and diversity in accordance with the Modern Standard Arabic (MSA) approach employed in online news articles. 867 football news articles were downloaded from Al-Jazeera.net to analyse the use of discourse markers (DMs) based on previous studies along with Modern Standard Arabic grammar books as well as the theories of Fraser (2005) and Al-Khawaldeh (2014). Both data coding and analysis were completed manually. The results showed that in linking textual fragments, discourse markers under the Additive category are the most frequently used within all the articles. In fact, the study also found that DM wa was most frequently used in articles compared to other discourse markers. For each category, the researcher discovered a set of new discourse markers that were not considered in previous works. The manual coding process has also led to the discovery of a new category – Affirmative, with a comprehensive list of discourse markers. It is hoped that this study can function as an important reference for researchers who are interested to delve deeper into the area.